FDI and macroeconomic stability: The Turkish case - İlyas Şıklar; Merve Kocaman (European Financial and Accounting Journal, 2018)
This study investigates the relationship between foreign direct investment (FDI) and macroeconomic stability for Turkey. To represent the macroeconomic stability, two main variables are examined. The first of these is inflation rate that represents the economic stability in real sector and the second one is real exchange rate representing the stability in the financial sector. In addition to these variables, the market size, openness to trade and financial development variables are also used as control-transmission variables. Used data are monthly and cover the period from January 2003 to April 2015. Empirical methods used in the study are unit root tests, cointegration analyses, vector error correction model (VECM) and Granger causality test. Obtained empirical results show that fluctuations in inflation and the real exchange rate have a negative and permanent effect on FDI, meaning that instabilities that occurred in real and financial markets negatively affected the inward FDI. Therefore Turkey, which has enough potential to attract FDI, has to provide stability in its macroeconomic indicators to attract a higher volume of FDI.
Keywords: E20; F21; 650; Foreign Direct Investment; Macroeconomic Stability; Turkish Economy